Knowledge and attitude about eye donation amongst anganwadi workers in a rural block of Pune district in India: a quasi experimental study - Barhate, Amruta; Pore, Prasad; Nath, Amol (International Journal Of Community Medicine And Public Health, 2020)
Background: Corneal diseases constitute a significant cause of visual impairment and blindness in India. Corneal transplantation is a major solution for this. In order to increase the corneal transplants, motivation of rural population is must to increase eye donation rates. Anganwadi workers (AWWs) constitute a major potential source of information in rural areas which needs to be educated to increase the procurement of corneas. The aims and objectives of the study was to compare the knowledge and attitude about eye donation amongst AWWs in rural Pune before and after intervention. Methods: The study was conducted in a randomly selected block of Pune. A pre-designed, pre-tested, anonymous, self-administered questionnaire was filled by the AWWs. A session on eye donation was conducted. The AWWs again filled the same questionnaire. Results: Study comprised of 86 AWWs, seventy-one (%) AWWs were aware about eye donation. Media was the main source of information followed by doctors. About 25.6% workers knew that cornea is the part of eye used for transplant. Eyes can be donated within 6 hours of death was known to 61.6% participants. A significant increase in the knowledge and attitude about eye donation occurred after intervention and most of them were willing to pledge for their eyes. Conclusions: Simple intervention in the form of lectures and short talks can make a significant change in the knowledge and attitude of AWWs.